Esophageal foreign bodies in adults: systematic review of the literature. (2nd November 2018) - Aiolfi, Alberto; Ferrari, Davide; Riva, Carlo Galdino; Toti, Francesco; Bonitta, Gianluca; Bonavina, Luigi
Abstract: Objective: Esophageal Foreign Body (FB) impaction represents a major challenge for healthcare providers. Aim of this systematic review was to analyse the current literature evidence on prevalence, presentation, treatment, and outcomes of impacted esophageal FB. Materials and methods: Literature search was conducted between 2000 and 30th June 2018 according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. Results: Sixty-one studies matched the inclusion criteria. The total number of included patients was 13, 092. The cervical esophagus was the most frequent impaction site (67%) and sharp-pointed objects were the most common FB (38.1%). Retrosternal pain (78%), dysphagia (48%), and odynophagia (43.4%) were the most common symptoms. A flexible or rigid endoscopic approach was adopted in 65.1% and 16.8% of patients, respectively. Overall, 17.8% of patients had a complication related to the impacted esophageal FB or to the endoscopic manoeuvers. A surgical approach was required in 3.4% of patients. The overall mortality was 0.85%. Conclusions: Surgery is the upfront treatment in patients with esophageal perforation or endoscopically irretrievable esophageal FB. A minimally invasive approach can be adopted in selected patients. Effective prevention of FB impaction should focus on accurate diagnostic work-up to search for an underlying motility disorder after a first episode of esophageal impaction, even if transient and self-resolving.